Two important examples of s.h.m. © D Hoult 2010
The mass / spring oscillator
The mass / spring oscillator
net force acting on the mass = zero
A graph of force against extension for a spring is a straight line passing through the origin: force a extension
A graph of force against extension for a spring is a straight line passing through the origin: force a extension The constant of proportionality, k is called the elastic constant of the spring (usually considered to be a positive number)
When the displacement is downwards, the net force is upwards and vice versa
So a better way to draw the graph would be
In this case, F represents the force with which the spring “pulls back” when it is given an extension x by some external agency
slope = - k
F = - k x
F = - k x If the mass is released after having been given a displacement, x, then its acceleration will be a =
F = - k x If the mass is released after having been given a displacement, x, then its acceleration will be - k x a = m
F = - k x If the mass is released after having been given a displacement, x, then its acceleration will be - k x a = m So the motion is s.h.m. and the constant of proportionality between a and x has magnitude
F = - k x If the mass is released after having been given a displacement, x, then its acceleration will be - k x a = m So the motion is s.h.m. and the constant of proportionality between a and x has magnitude k m
F = - k x If the mass is released after having been given a displacement, x, then its acceleration will be - k x a = m So the motion is s.h.m. and the constant of proportionality between a and x has magnitude k m which is equal to w2 in the “shm equation”
Remembering that 2p T = w we can suggest that the time period of a mass spring oscillator is given by
Remembering that 2p T = w we can suggest that the time period of a mass spring oscillator is given by m T = 2p k
The simple pendulum
F =
F = mg sin q
F =
F = - mg sin q
a =
a = - g sin q
q =
x q = L
If we make sure that q is a small angle
If we make sure that q is a small angle, sin q can be replaced by q
g a = - x L